Federal Debt Management, 1953-58 - Hallowell, Burton C.; Williamson, Kossuth M. (The Review of Economics and Statistics, 1963)
T HIS paper examines the effects of debt management on aggregate expenditure during I9 53-58. The Treasury in this period lengthened the debt in recession and allowed it to shorten somewhat in prosperity (Table i), the opposite of the anti-cyclical policy advocated by some economists. Treasury policy was defended on the grounds that it did not unduly intensify recessions and that offerings of longterm securities in prosperity provided undesirable competition with new issues of private, state, and local government securities and increased interest costs.1 Debt management for purposes of this paper